Peningkatan Keterampilan dan Kesadaran Masyarakat Tenjolaya Melalui Pendekatan Komprehensif Untuk Efisiensi - Hana Rengganawati; Santi Widiawati; Salim, Agus; Irwan Hermawan (Darma Abdi Karya, 2024)
This research stems from the implementation of Kuliah Kerja Nyata (KKN) in Tenjolaya Village, Bandung Regency, involving students in intensive observation. KKN, as a student dedication activity, aims to have a positive impact on the community through coordination with government, education and UMKM, and local communities. This observation, as the main foundation of the KKN work program, opens up problem horizons in Tenjolaya Village. The issues include a lack of understanding among PKK mothers regarding Microsoft Excel, insufficient awareness of students regarding cyberbullying impacts, and a lack of students' confidence in career prospects. In the UMKM sector, dependence on the owner and one workforce is a constraint, coupled with the expansion of online marketing strategies. The research focus also includes increasing the capacity and involvement of Karang Taruna in RW 09 and RW 10. The research methodology adopts a qualitative approach with participatory observation during KKN. This study targets the improvement of understanding and skills among PKK mothers in using Microsoft Excel, educational administration efficiency, students' confidence in career prospects, students' understanding of productive department material, promotion of students' habits in foreign language learning, reducing UMKM dependence on the owner and one workforce, and increasing the capacity and involvement of Karang Taruna in RW 09 and RW 10. Thus, this research strives to provide sustainable solutions to enhance community skills and awareness. The achievement is directed toward efficiency to support holistic development in various sectors. The research results are expected to contribute positively to the welfare and development of the Tenjolaya community, bringing broader positive impacts at the local level. The final conclusion emphasizes the urgency of sustained and holistic efforts to achieve efficiency across all layers of society.